Nurse-physician collaboration, intention to leave job, and professional commitment among new graduate nurses - Tarhan, Merve; Doğan, Pınar; Kürklü, Ahu (Wiley, 2022)
Background: The quality of communication and collaboration with colleagues, managers, and physicians affects the intention to leave a job and the profession for new graduate nurses (NGNs). New graduates have difficulties communicating and collaborating with physicians, especially. Aim: This study aimed to determine the relationship between the attitudes of nurse-physician collaboration and the levels of intention to leave the current job and professional commitment among NGNs. Methodology: This descriptive, cross-sectional study was carried out with 231 NGNs in four private hospitals affiliated with an university. Data were collected by using a self-administered questionnaire, including a personal information form, the Jefferson Scale of Attitudes towards Physician-Nurse Collaboration, Intention to Leave Scale, and Nursing Professional Commitment Scale. Data analysis was performed using descriptive statistics, and Spearman's rank correlation coefficients. Results: NGNs had a high positive attitude towards nurse-physician collaboration with a median score of 49 (45-54). The professional commitment of NGNs was high level with a median score of 75 (69-86). The intention to leave the current job median score was 3 (2.3-3.6) out of 5. There was a statistically significant correlation between attitudes towards nurse-physician collaboration and the levels of intention to leave the current job (r(s) = -0.22; p < 0.01) and professional commitment (r(s )= 0.42; p < 0.01). Conclusion: The results showed that improving NGNs' attitudes towards nurse-physician collaboration increases the professional commitment and reduces turnover intention.
Keywords: Interprofessional Relations; Nurses; Personnel Turnover; Physician?Nurse Relations; Physicians